OCCURRENCE AND COMPLICATIONS OF SUPERNUMERARY TEETH AMONG PEOPLE LIVING IN GOMBE STATE, NIGERIA - RAYYANU Z. S.; MUHAMMAD H. B.; ABDULLAHI N. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2020)
The present study is aimed to evaluate the occurrence and complications of supernumerary teeth among people living in Gombe State, Nigeria. The total number of 300 individuals with an equal number of males (n=150) and females (n=150) with ages ranges from 5-78 years attending the dental clinic, specialist hospital Gombe for different reasons of dental complain and routine dental check-up were randomly selected for this research. The data was collected with the subject sited on a chair under a sunlight. The oral examination was carried out using a mouth mirror, hand gloves, and a blunt probe. The teeth were cleaned of food debris with cotton wool for proper visibility. The observed supernumerary teeth were classified under different classifications. The obtained data were subjected to Chi-squared test to obtain differences in supernumerary teeth distribution using SPSS version 20.0 software (IBM Corporation, USA). The result shows a 5.2% prevalence of supernumerary teeth in which is more in the incisor presented 3.39 %. The location was more in the maxillary arch 90 % (n = 311), about 35.8% (n = 124) of the supernumerary teeth were erupted. This study finds that the frequency of supernumerary teeth was higher in children (5-10 years), which is more around the incisor of the maxillary region, in which most of them have singly erupted and asymptomatic. However, some of them are accompanied by some symptoms like impaction, crowding, and displacement.